(untitled) (Revista Inclusiones, 2020)
The urgency of the problem under investigation is conditioned by the need to strengthen and preserve student youth’s health. This is one of the main tasks facing the Ufa State Petrolium Technical University (USPTU) today. The purpose of the article is to develop, theoretically substantiate and introduce into the learning process various forms of healthy walking aimed at implementing effective methods of disease prevention. Healthy walking forms described in the article allow improving physical state, identifying physical and functional conditions, psycho-emotional state. The students from the special medical group (SMG) were divided into two groups – experimental and control. The first group was characterized by more significant growth in functional state indicators than the second one, to which were applied those physical education facilities that are provided for by the physical education program for higher education institutions. This indicates the effectiveness of the applied forms of healthy walking. The materials of the article can be useful for PE instructors working in educational institutions.